Implementation of the Communication Strategy of Bank BPR Bandung Collectors in Reducing the Number of Defaults - Putra, Feby Nugraha; Putri, Sekartaji Anisa (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
The phenomenon of credit default in the banking sector is concerning in the post-pandemic era, particularly for small-scale financial institutions, such as Rural Credit Banks (BPR). This study analyses the communication strategies used by collectors at Rural Credit Bank (BPR)